The role of cardiac computed tomography in predicting adverse coronary events - Emfietzoglou, Maria; Mavrogiannis, Michail C.; Samaras, Athanasios; Rampidis, Georgios P.; Giannakoulas, George; Kampaktsis, Polydoros N. (Frontiers in Cardiovascular Medicine, 2022)
Cardiac computed tomography (CT) is now considered a first-line diagnostic test for suspected coronary artery disease providing a non-invasive, qualitative, and quantitative assessment of the coronary arteries and pericoronary regions. Cardiac CT assesses vascular calcification and coronary lumen narrowing, measures total plaque burden, identifies plaque composition and high-risk plaque features and can even assist with hemodynamic evaluation of coronary lesions. Recent research focuses on computing coronary endothelial shear stress, a potent modulator in the development and progression of atherosclerosis, as well as differentiating an inflammatory from a non-inflammatory percoronary artery environment using the simple measurement of pericoronary fat attenuation index. In the present review, we discuss the role of the above in the diagnosis of coronary atherosclerosis and prediction of adverse cardiovascular events. Additionally, we review the current limitations of cardiac computed tomography as an imaging modality and highlight how rapid technological advancements can boost its capacity in predicting cardiovascular risk and guiding clinical decision-making.